Periodic dietary restriction of animal products induces metabolic reprogramming in humans with effects on cardiometabolic health - Konstantinos Rouskas; Ozvan Bocher; Alexandros Simistiras; Christina Emmanouil; Panagiotis Mantas; Anargyros Skoulakis; Young-Chan Park; Alexandros Dimopoulos; Stavros Glentis; Gabi Kastenmüller; Eleftheria Zeggini; Antigone S. Dimas (npj Metabolic Health and Disease)
Abstract Dietary interventions constitute powerful approaches for disease prevention and treatment. However, the molecular mechanisms through which diet affects health remain underexplored in humans. Here, we compare plasma metabolomic and proteomic profiles between dietary states for a unique group of individuals who alternate between omnivory and restriction of animal products for religious reasons. We find that short-term restriction drives reductions in levels of lipid classes and of branched-chain amino acids, not detected in a control group of individuals, and results in metabolic profiles associated with decreased risk for all-cause mortality. We show that 23% of proteins whose levels are affected by dietary restriction are druggable targets and reveal that pro-longevity hormone FGF21 and seven additional proteins (FOLR2, SUMF2, HAVCR1, PLA2G1B, OXT, SPP1, HPGDS) display the greatest magnitude of change. Through Mendelian randomization we demonstrate potentially causal effects of FGF21 and HAVCR1 on risk for type 2 diabetes, of HPGDS on BMI, and of OXT on risk for lacunar stroke. Collectively, we find that restriction-associated reprogramming improves metabolic health and emphasise high-value targets for pharmacological intervention.